REGULATORY T–CELLS: ORIGIN AND FUNCTION - I. S. Freidlin (Медицинская иммунология, 2014)
Abstract. Over the past decade a population of so–called “regulatory T cells” (Treg cells) has been linked to the prevention of autoimmunity. In this review we discuss the molecular mechanisms of Treg cells development and function including the identification of the unique molecular marker of Treg cells – the transcription factor Foxp3. We discuss also the mechanisms of suppression, which include the direct cell contact through binding of cell surface molecules CTLA–4 on Treg cells to CD80/CD86 molecules of effector T cells and the local secretion of cytokines (IL–10, TGFβ). Deficiency in or dysfunction of these cells can be a cause of autoimmune disease. These cells are a good target for designing ways to induce or abrogate immunological tolerance to self and non–self antigens. (Med. Immunol., 2005, vol.7, № 4, pp. 347–354)